Analisis Perancangan Sistem Informasi Tanivest terhadap Penjualan Hasil Tani di Indonesia (Current Research in Education: Conference Series Journal, 2022)
Tanivest is a website-based e-commerce information system that focuses on the sale of crops from farmers throughout Indonesia. Tanivest is made to make it easier for customers to buy a product from the harvest that he needs. Customers only need registration using the email address, no-mobile phone and password so that the customer can enter the website and can transact easily. The research method used is the SDLC (System Development Life Cycle) approach model with the waterfall model. Tanivest Information System was created with the aim of the welfare of farmers' lives, handling the management of business processes run by Tanivest e-commerce, handling the management of Agricultural Products data, handling member data management, and handling the management of Transaction Report data.  Keywords: Digitization, E-commerce, Tanivest